Introspecting entrepreneurship from Tawhidic perspective / Farah Akmar Anor Salim ... [et al.] - Salim, Farah Akmar Anor; Mhd Sarif, Suhaimi; Maidin, Ainul Jaria; Ismail, Yusof; Zainudin, Dolhadi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
The concept of ethical attitude and standard in business dealings has long been argued in the academic world.  The current implication on skills and ethical concepts and ideas of Malaysian entrepreneurs from Islamic practices is briefly outlined in the study.  Capitalizing on a comprehensive set of questionnaire containing information on respondent's profile, characteristics and educational background, one hundred twenty one (121) entrepreneurs were surveyed using convenience sampling.  The practices of Islamic skills and ethics among Malaysian entrepreneurs in numerous business sectors are discussed in the study. The study postulates that the awareness gained from well-being (falāh) in life and excellence (itqān) in work from business organisation can be derived from the pursuit of Tawhidic principle.  A set of close ended questions that contains individual's characteristics and principles are distributed to entrepreneurs from various business sectors and work experiences for the purpose.  Providentially, the study managed to collect 121 completed questionnaires from Malaysian's entrepreneurs. The study contributes significant information to the academic world as well as to the corporations and governments in conducting business.  Finally, the study concludes with the discussion on the proposed business practices and recommended future implementation in achieving entrepreneur's career success.